COMMUNICATION AND ORGANIZATIONAL CULTURE INFLUENCE ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION - agus, agustim; Agustim, Warter; Ratna, Jensiana (Universitas Islam Lamongan, 2024)
The purpose of this study is to determine the influence of communication and organizational culture on employee performance through job satisfaction. This research uses quantitative methods. The study population was 32 employees at the Malang City Population and Civil Registration Office which was conducted by census. Data collection using questionnaires. The data analysis method used is Smart PLS. The results of the study proved that communication directly has a significant effect on job satisfaction, organizational culture has a significant effect on job satisfaction, communication has a significant effect on employee performance, organizational culture has a significant effect on employee performance and job satisfaction has a significant effect on employee performance. The results are indirectly known that communication has a significant effect on employee performance through job satisfaction and organizational culture has a significant effect on employee performance through job satisfaction. This result can be understood that good communication and organizational culture will create job satisfaction so as to support the improvement of employee performance